(untitled) (Physical Education, Health and Social Sciences, 2026)
Hepatitis C in humans is an inflammation of the liver cells brought on by HCV. The infection is typically subclinical, but if it manifests, it can cause liver fibrosis, which can progress to cirrhosis. Cirrhosis patients may experience liver collapse and other consequences, such as hepatocellular carcinoma. From October 2012 to March 2013, a cross-sectional study was carried out to ascertain the frequency distribution of active hepatitis C virus (HCV) infection among people of District Hangu KPK, Pakistan, who appeared to be in good health. Random blood collection was used to investigate residents of all ages and genders. This study involved surveying 400 people, 223 of whom were men and 177 of whom were women. Participants in the study ranged in age from 10 to 65. Each participant completed a detailed history on a questionnaire. Using the ELISA technique, all research participants were first checked for anti-HCV antibodies. In order to detect HCV-RNA and do additional screening, the ELISA-positive samples were analyzed using the polymerase chain reaction (PCR). The findings showed that while 7.5% of the general population had anti-HCV antibodies in their blood, 4.5% of the people in District Hangu KPK, Pakistan, are actively infected with the hepatitis C virus (HCV). Additionally, it was shown that males had a greater frequency of active Hepatitis C virus infection (2.75%) than females (1.75%). As the population’s age increases, so does the proportionality of HCV prevalence. Those aged 46–65 years had an exceptionally high prevalence of HCV (2.00%), followed by those aged 26–45 years with a moderate prevalence (1.75%), and those aged 5–25 years with a low prevalence rate (0.75%).